Successful mRNA SARS-Cov-2 vaccine rechallenge after a first episode of immune thrombocytopenic purpura - Mathilde Chanut; Rym Jaidi; Milena Kohn; Thomas Grange; Clara Brones; Naëlle Lombion; Philippe Rousselot; Thomas Longval (Platelets, 2022)
In 2021, the world experienced the most extensive vaccination campaign to defeat COVID-19. Many cases of idiopathic thrombocytopenia have been reported following injections of SARS-Cov-2 mRNA vaccine. We present the case of a 73-year-old woman with de novo ITP after a first injection of SARS-Cov-2 mRNA vaccine (Moderna vaccine) who experienced a successful rechallenge of SARS-Cov-2 mRNA vaccine (Pfizer vaccine) a few months later.